2022
DOI: 10.1029/2021gl097450
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Forcing of Martian Climate Revealed in a South Polar Outlier Ice Deposit

Abstract: The northern (NPLD) and southern (SPLD) polar layered deposits of Mars contain stratigraphic sequences of ice and dust that have been extensively studied as paleoclimate records (see review in Byrne, 2009). It has been hypothesized for decades that these records are controlled by Mars' orbital and rotational variations (e.g., Cutts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…So, while Burroughs may have formed under similar environmental conditions, it is unlikely to be a remnant of a more extensive SPLD. This dissimilarity between Burroughs and SPLD radar stratigraphy is consistent with the lack of match found between Burroughs and SPLD's exposed visible layering using dynamic time warping (Sori et al, 2014(Sori et al, , 2022. Sori et al (2022) concluded that the Burroughs deposit contains an orbitally controlled climate record and was likely emplaced over the last 4.5 Myr, which would result in the Burroughs deposit carrying a climate record that is entirely separate from the SPLD, which has a surface age of at least 10 Ma (Herkenhoff & Plaut, 2000).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…So, while Burroughs may have formed under similar environmental conditions, it is unlikely to be a remnant of a more extensive SPLD. This dissimilarity between Burroughs and SPLD radar stratigraphy is consistent with the lack of match found between Burroughs and SPLD's exposed visible layering using dynamic time warping (Sori et al, 2014(Sori et al, , 2022. Sori et al (2022) concluded that the Burroughs deposit contains an orbitally controlled climate record and was likely emplaced over the last 4.5 Myr, which would result in the Burroughs deposit carrying a climate record that is entirely separate from the SPLD, which has a surface age of at least 10 Ma (Herkenhoff & Plaut, 2000).…”
Section: Discussionsupporting
confidence: 58%
“…Sori et al. (2022) concluded that the Burroughs deposit contains an orbitally controlled climate record and was likely emplaced over the last 4.5 Myr, which would result in the Burroughs deposit carrying a climate record that is entirely separate from the SPLD, which has a surface age of at least 10 Ma (Herkenhoff & Plaut, 2000). Our findings support this result, and we find that in addition to recording a different climate history than the SPLD (and therefore the marginal group), Burroughs may also record a different history than the Reynolds group.…”
Section: Discussionmentioning
confidence: 99%
“…Myr‐average H 2 O‐ice‐plus‐dust deposition rates calculated from the SPLD (from >∼10 Myr ago; Becerra et al., 2019), Burroughs crater (∼0–4.5 Myr; 72.3°S, 116.6°E; Sori et al., 2022), and NPLD (∼0–4.5 Myr; e.g., Hvidberg et al., 2012; Becerra et al., 2017) records are 0.13–0.39, 0.13, and 0.55 mm yr −1 , respectively. Section 3 best‐fit equations yield a comparable average 510‐kyr MCID rH2normalO ${r}_{{\mathrm{H}}_{2}\mathrm{O}}$ = 12 mm yr −1 (Region 1) and 0.25 mm yr −1 (Region 2).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, ∼3 × 10 12 kg of H 2 O ice participates in an equilibrated seasonal sublimation-deposition cycle. Approximately one-third exchanges between hemispheres and ∼two-thirds recycles within the northern hemisphere (Montmessin et al, 2017).Previous studies of H 2 O ice and dust layers in the North and South Polar Layered Deposits (NPLD, SPLD) and near-polar ice deposits extracted ∼0.1-0.5 mm yr −1 deposition rates averaged over a few Myr using wavelet analysis (Becerra et al, 2017(Becerra et al, , 2019Sori et al, 2022) and simplified stratigraphic development modeling (Hvidberg et al, 2012). However, these averaging timescales are much longer than orbital element periodicities, the deposits have loose temporal constraints (Tanaka et al, 2008), and no model has yet produced a one-to-one correlation between modeled and observed layers in these deposits (Hvidberg et al, 2012;Levrard et al, 2007).…”
mentioning
confidence: 99%
“…The present work provides insight into Mars' south polar 𝑟 𝐻 2 𝑂 over the past ~510 kyr, a different record than targeted by previous quantitative analysis. Previous polar layer analyses include: (1) South Polar Layered Deposit (PLD) records (Becerra et al, 2019), which likely reflect a climate from 10s of Myr ago (Herkenhoff & Plaut, 2000;Koutnik et al, 2002); the Burroughs crater record (72.3°S, 116.6°E;Sori et al, 2022) reflects deposition over ~4.5 Myr in a different environment, both spatially distant and lacking a perennial CO 2 cold trap; (3) North PLD records (e.g., Hvidberg et al, 2012;Becerra et al, 2017) from the past ~1 Myr.…”
Section: Long-term H 2 O Deposition Ratesmentioning
confidence: 99%